Coordinated operation and optimal sizing strategy of P2G—CNG trucks scheme on wind farm for participating in retail gas market - Salimu, Athuman; Zhang, Feng; Zhang, Gang; Yang, Libin (Frontiers in Energy Research, 2024)
The increase in wind penetration and the stochastic nature of wind cause some wind power to be curtailed, leading to a loss of revenue. Wind farm owners can invest in power to gas (P2G)compressed natural gas (CNG) truck systems to utilize the curtailed wind power that would otherwise have been wasted. This paper proposes coordinated operation and optimal sizing strategy of P2G and (CNG) trucks. P2G derives its power from curtailed wind power and also purchases electricity at low prices to facilitate methane (natural gas) production. The methane is directly stored in CNG trucks, which are used as temporary storage and as a means of transporting the gas, thereby reducing the costs by eliminating storage tank. Firstly, a coordinated operation strategy for P2G and CNG trucks considering curtailed wind power and electricity purchased from the grid is presented. Secondly, an optimal sizing optimization model to determine the capacity of P2G and the number of CNG trucks using particle swarm optimization is presented, considering the coordinated operation strategy and operation constraints to maximize profit when the proposed system participates in the retail gas market. Finally, case studies were conducted to verify the viability of the proposed strategy using curtailed wind power data, electricity price data, and gas price data. Results show that the proposed strategy led to profit by selling the produced natural gas to a retail gas market. The optimal capacity of the P2G plant is 9.9 MW, and the optimal number of CNG trucks is 2. There is a 19.8% cost reduction with a payback period of 5.728 years compared to the conventional strategy with a payback period of 8.52 years. 89.74% of curtailed wind power is utilized, while only 10.26% of curtailed wind power is wasted due to operating constraints of the system.